A highly reproducible cervical cuff technique for rat‐to‐mouse heterotopic heart xenotransplantation. (19th August 2017) - Li, Yaguang; Xie, Baiyi; Zhu, Maoshu; Li, Xianguo; Du, Feifei; Li, Yanping; Li, Minghui; Yuan, Qian; Hua, Jianyu; Xue, Mengjiao; Wang, Zhenzhen; Xia, Junjie; et al.
Abstract: Xenotransplantation is an effective way to solve the problem of donor shortage in clinical transplantation. However, clinical use of xenotransplantation is currently limited due to immunological challenges such as acute vascular rejection and cell‐mediated rejection. To finally surpass this immunological barrier, more preclinical research is needed into the molecular mechanisms of rejection and the possible effects of new immunosuppressants. Our aim was to create a refined, highly reproducible protocol to establish the most suitable rat‐to‐mouse heterotopic heart transplantation model using the cuff technique.